KAJIAN EKONOMI SEKTOR PERTANIAN DI KABUPATEN JEMBER - Tia Napitupulu; Aulia Nadhirah; Sumarlina; Amalia Dwi Marseva (Journal of Agricultural Socio-Economics (JASE), 2023)
The agricultural sector has a big role in national development through regional development, one of which is in the Jember Regency. This study aims to analyze an overview of the condition of the agricultural sector in Jember Regency, the role of the agricultural sector in terms of competitive advantage, and analyze economic growth in Jember Regency. The data used in this study is secondary data, namely data on Gross Regional Domestic Product (GDP) at constant prices for the period of the year 2017 – 2021. The data that has been collected is then analyzed using 3 (three) analytical methods including Klassen typology analysis, Location Quotient analysis (LQ), and shift-share analysis. The results showed that: (1) based on the results of the Klassen typology analysis, the agricultural sector in Jember Regency is included in the depressed growth sector category; (2) the agricultural sector is the base sector, which has the largest LQ value compared to other sectors; and (3) there is an increase in economic growth in the agricultural sector in Jember Regency, although it is slower than other sectors.